2015
DOI: 10.1166/jnn.2015.11191
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte/Graphene Oxide Barrier Film for Flexible OLED

Abstract: Ultra-thin flexible nano-composite barrier layer consists of graphene oxide and polyelectrolyte was prepared using the layer-by-layer processing method. Microstructures of the barrier layer was optimized via modifying coating conditions and inducing chemical reactions. Although the barrier layer consists of hydrophilic polyelectrolyte was not effective in blocking the water vapor permeation, the chemical reduction of graphene oxide as well as conversion of polyelectrolyte to hydrophobic nature were very effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They have great potential in the substitution of the commonly used indium tin oxide (ITO), which has inevitable limitations for applications in flexible electronics due to its fragility, high cost, and harsh preparation conditions. 1,2 Thus, various alternative materials, such as graphene, 3,4 carbon nanotubes (CNTs), 5 metallic nanowires, 2,6,7 and conductive polymers, 8 that can replace ITO have drawn increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…They have great potential in the substitution of the commonly used indium tin oxide (ITO), which has inevitable limitations for applications in flexible electronics due to its fragility, high cost, and harsh preparation conditions. 1,2 Thus, various alternative materials, such as graphene, 3,4 carbon nanotubes (CNTs), 5 metallic nanowires, 2,6,7 and conductive polymers, 8 that can replace ITO have drawn increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) is a single‐layer material with various oxygen‐containing groups (mainly epoxy and hydroxyl groups) that enable attractive properties like extreme thickness and smoothness, strong mechanical strength, high specific surface area, optical transmittance etc. Since the discovery of graphene and its functionalized derivative graphene oxide, hybrid PEM/GO films have attracted considerable attention due to their fascinating properties and fields of application, for example, in nanocapsules for drug‐delivery, sensors with ultrahigh sensitivity, photoconductive films for microelectronic fabrication, hybrid transparent films with controllable conductivity and improved gas‐barrier and mechanical properties . Therefore, knowledge of the factors that control the properties of PEM/GO films is indispensable for fabrication of films for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to compare and contrast the surface properties of nanocomposite materials based on PE‐matrix (of strong synthetic or weak natural PE) and non‐polymeric component (GO) added on top or in‐between PE‐layers. In the recent years several studies reported on construction of PEM/GO films comprising strong synthetic polyelectrolytes such as polyethylenimine (PEI), polydiallyldimethylammonium chloride (PDDA), and polyallylamine hydrochloride (PAH) but they are mainly focused on examination of the conductivity, transparency, gas‐barrier, and mechanical properties. Here we built hybrid, nanometer‐thick films composed of strongly charged synthetic poly(sodium 4‐styrenesulfonate)/poly(diallyldimethylammonium chloride) (PSS/PDDA) and weakly charged natural hyaluronic acid/chitosan (HA/Chi) polyelectrolyte pairs, containing various proportions of GO‐layers and studied the impact of GO incorporation into PE‐matrices on their growth mechanism, thickness, topology, roughness, and hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%